A deterministic method of distributed generation hosting capacity calculation: case study of underground distribution grid in Morocco - soukaina naciri; Ismail Moufid; Hassan El Moussaoui; Tijani Lamhamdi; Hassane El Markhi (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Global warming has become a significant concern over the past decades. As a result, governments have shifted their policies toward renewable energy sources and environmentally friendly industries. This approach requires a renewal of the electrical networks to accommodate this new intermittent generation (from solar and wind sources) while remaining stable and reliable. In this vision, the notion of hosting capacity has been introduced to define the amount of new distributed generation that an electrical network can host without affecting its stability and reliability. This study proposes a deterministic method based on the π model of cables to estimate the underground feeder's hosting capacity. This method considers reverse power flow, overvoltage, reconfiguration, overloading, and the physical characteristics of lines. It is applied to the Moroccan medium voltage underground radial feeder. Through DIgSILENT power factory software, the power flow analysis is carried out to validate its effectiveness in overcoming overvoltage and cable overload problems. The results validate the relevance of our method, its reliability, its fluidity of application, and its ability to maintain performance indices within the acceptable range.